Ответ:
13 ; 1
Объяснение:
ODZ:
(x^2-6x+13)≠0 x^2-8x+13≠0
D<0 ⇒ x∈R D=64-52=12 ⇒ D=√12 ⇒ D=2√3 ⇒ x≠(8±2√3)/2=x≠4±√3</p>
Разделим на x каждое уравнение :
ODZ: x≠0
Пусть x+13/x = t
![\frac{t-10}{t-6} =\frac{3}{t-8} \\t\neq 6;8\\(t-10)(t-8)=(t-6)3\\t^2-8t-10t+80=3t-18\\t^2-8t-10t+80-3t+18=0\\t^2-21t+98=0\\D=441-392=49\\\sqrt{49} =7\\x=\frac{21+-7}{2} =14;7 \frac{t-10}{t-6} =\frac{3}{t-8} \\t\neq 6;8\\(t-10)(t-8)=(t-6)3\\t^2-8t-10t+80=3t-18\\t^2-8t-10t+80-3t+18=0\\t^2-21t+98=0\\D=441-392=49\\\sqrt{49} =7\\x=\frac{21+-7}{2} =14;7](https://tex.z-dn.net/?f=%5Cfrac%7Bt-10%7D%7Bt-6%7D%20%3D%5Cfrac%7B3%7D%7Bt-8%7D%20%5C%5Ct%5Cneq%206%3B8%5C%5C%28t-10%29%28t-8%29%3D%28t-6%293%5C%5Ct%5E2-8t-10t%2B80%3D3t-18%5C%5Ct%5E2-8t-10t%2B80-3t%2B18%3D0%5C%5Ct%5E2-21t%2B98%3D0%5C%5CD%3D441-392%3D49%5C%5C%5Csqrt%7B49%7D%20%3D7%5C%5Cx%3D%5Cfrac%7B21%2B-7%7D%7B2%7D%20%3D14%3B7)
Обратная замена :
И:
![x+\frac{13}{x} =7\\x\neq 0\\x^2+13=7x\\x^2+13-7x=0\\x^2-7x+13=0\\D=49-52= -3 x+\frac{13}{x} =7\\x\neq 0\\x^2+13=7x\\x^2+13-7x=0\\x^2-7x+13=0\\D=49-52= -3](https://tex.z-dn.net/?f=x%2B%5Cfrac%7B13%7D%7Bx%7D%20%3D7%5C%5Cx%5Cneq%200%5C%5Cx%5E2%2B13%3D7x%5C%5Cx%5E2%2B13-7x%3D0%5C%5Cx%5E2-7x%2B13%3D0%5C%5CD%3D49-52%3D%20-3)
Так как D<0 , данное уравнение действительных корней не имеет.</p>
Получим корни : 13;1